Examining the Influence of Electronic Word-of-Mouth on Consumer Purchasing Behavior: The Mediating Role of Customer Trust in Driving Conversion Optimization - Amin, Shaheera; Tufail, Muhammad Sajid; Ali, Muhammad Hasnain; Bashir, Furrukh (Pakistan Journal of Humanities and Social Sciences, 2025)
In the modern electronic market, electronic word-of-mouth (eWOM) is a strong driver of consumer behaviour, particularly when used alongside customer reliability and website performance rates like Conversion Rate Optimization (CRO). In examining these associations, the paper relies on both Social Exchange Theory and the Technology Acceptance Model. As the theoretical frameworks, the study was done using a quantitative and cross-sectional research design, where 300 structured questionnaires were administered to primary data (online consumers in Pakistan). The data analyses relied on SmartPLS 3.28 with measurement and structural model analysis and bootstrapping methodology to test the hypotheses. The results indicate that eWOM directly affects customer trust and purchasing behavior significantly, and customer trust mediates the connection between eWOM and two outcome variables, which are CRO and consumer purchasing behavior. These findings demonstrate the critical importance of trust as a psychological process increasing the effectiveness of conversion and purchase intentions in online settings. Marketers can find useful information in this research when optimizing online platforms by using the content generated by users and strategies to build trust. There are also implications, limitations, and future research directions.